2002
DOI: 10.1542/peds.110.4.772
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Prone Sleeping Position to the Racial Disparity in Sudden Infant Death Syndrome: The Chicago Infant Mortality Study

Abstract: Prone sleeping was found to be a significant risk factor for SIDS in this primarily African American urban sample, and approximately one third of the SIDS deaths could be attributed to this factor. Greater and more effective educational outreach must be extended to African American families and the health personnel serving them to reduce prone prevalence during sleep, which appears, in part, to contribute to the higher rates of SIDS among African American infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 51 publications
2
69
0
1
Order By: Relevance
“…Hauck, et al, in a case-control study of SIDS, found that 58% of African-American infants bedshared, compared with 29.2% of non-African-American infants. (30) Similarly, in a retrospective population-based cohort of sudden unexpected infant deaths, Unger et al found bedsharing deaths to be nearly twice as common in African American infants. (24) Other studies have found bedsharing to be linked to measures of poverty.…”
Section: Discussionmentioning
confidence: 96%
“…Hauck, et al, in a case-control study of SIDS, found that 58% of African-American infants bedshared, compared with 29.2% of non-African-American infants. (30) Similarly, in a retrospective population-based cohort of sudden unexpected infant deaths, Unger et al found bedsharing deaths to be nearly twice as common in African American infants. (24) Other studies have found bedsharing to be linked to measures of poverty.…”
Section: Discussionmentioning
confidence: 96%
“…Our results substantiate what other studies have found regarding racial and ethnic differences in the leading causes of infant death. 8,[19][20][21] Several studies have found ethnic differences in dietary (folic acid intake), 22 genetic, 23 environmental, 20 and health service factors, 19,24 and these variations may lead to ethnic differences in cause of infant death. In the case of SIDS, the Chicago Infant Mortality Study 20 found that black women were more likely to put their in- Cause of Death (ICD-9-CM) Rate Per 100 000 Live Births for Neonatal (N) and Postneonatal (P) Mortality, by Maternal Ethnicity: California, 1995California, -1997 Cause of Death (ICD-9-CM Code)…”
mentioning
confidence: 99%
“…The prone and side sleeping positions increase the risk of sudden and unexplained infant death during any sleep, including napping. 30 However, caregivers may be less aware or less concerned about the infant' s sleeping position if they believe that they will be awake and observing the infant. 31 Anecdotal data suggest that parents often place their infants on sofas when they will be in the same room and want the infant within sight (R.Y.M., unpublished data).…”
Section: Discussionmentioning
confidence: 99%